Direct comparison of immunological effects of various nutritional supplements - Vaclav Vetvicka (临床与病理杂志, 2021)
Objective: Immunonutrition represents a diet based on the knowledge of basic principles of the immune system and its functions. Despite numerous claims, the direct comparison of the immunostimulating effects of natural modulators is limited, making any conclusions difficult. Our study focused on most common vitamins and immunonutrients and directly compared their effects on various branches of the immune system. Methods: In this study we used a mouse model to evaluate various aspects of immune reactions, namely phagocytic activity, IL-2 secretion, NK cell activity, antibody formation and growth of breast cancer in order to find out the possible effects of six different immunonutrients and their combinations. Results: We found that glucan was in all tests the most active immunomodulator. Synergistic effects were observed only in glucan-selenium and glucan-vitamin C combinations. The rest of immunonutrients had only small activity or no activity at all. Conclusion: Based on our results, we concluded that most of vitamins and minerals have only limited, if any, effects on immune activities including cancer. The current study managed to confirm synergistic effects of the beta glucan-vitamin C and beta-glucan-selenium combinations. More studies on possible positive or negative effects of such combination and on mechanisms of action are important.